Testes fisioterapêuticos de fácil acesso para realização de avaliação pré-temporada em membros inferiores no âmbito esportivo - revisão de literatura - Bianca Carneiro de Santana (2023)
Introduction: Imbalances and movement changes are often related to the occurrence of pain or injury in the lower limbs, especially in sports. In addition to days off work, sports injuries generate deficits in the athlete's performance and mental health, as well as high costs for clubs. Considering the factors related to sports injuries and the consequences that an injury can bring to the athlete or team, pre-season assessments are commonly performed to identify athletes with deficits and at high risk of developing an injury. The information obtained in a pre-season evaluation allows the formulation of training programs for individual athletes, approaching the deficits presented by each one, or by the team, aiming to prevent future deficits and/or injuries. Aim: To review in the available literature the physical-functional tests of the lower limbs that are easily accessible for pre-season assessments in athletes and that allow the identification of risk factors for more recurrent injuries. Methodology: The present study is a literature review. Published articles from the period 2000-2022, in Portuguese and English, which carried out evaluative tests in a healthy population, men and women, practicing various sports from recreational to professional levels, were included. Results: 64 articles were identified. After removing duplicates, articles were selected using inclusion and exclusion criteria. Thus, in the end, 14 articles were included in this review. The available literature shows that the use of physical-functional tests of the lower limbs that are easy to access and reproduce, such as those presented in this review, can be used to carry out pre-season assessments and identify risk factors for injuries in athletes from different modalities. In addition, all tests brought in this review are validated and have proven to be effective and are easy to access and execute to carry out pre-season evaluations. Conclusion: The present study can help in the elaboration of a pre-season evaluation from the use of the tests discussed here, since they allow the examiner to capture important and objective information that will compose the evaluation picture of his athlete.